AKRAB MANAJEMEN KRISIS UNIVERSITAS ISLAM INDONESIA (UII), YOGYAKARTA DALAM MENGATASI KASUS MAPALA UNISI - Halimatus Sa’diyah (Jurnal Ilmu Komunikasi AKRAB, 2017)
AbstractUniversitas Islam Indonesia (UII) is the oldest and the largest Islamic university in Yogyakarta (DIY), which in early 2017 was in crisis. The crisis caused by the death of three students who attend pendidikan dasarunit kegiatan mahasiswa (UKM) mahasiswa pecinta alam (Mapala) UNISI. The research’s goal is to determine the UII’s communication activities to response the crisis. This research used qualitative content analysis using newspaper like Harian Jogja, Kedaulatan Raykat and media releases on the official website of UII. Crisis management with Three-Stage Approach is used as the theory. The results showed that the communication activities in the stage of crisis event (crisis) are (1) established a crisis center (crisis team) and an internal investigation team; (2) delivereda formal statement and create releases; (3) apology and responsibility to the victims; (4) closed Mapala UNISI organizations and activities; (5) The rector and vice rector III resigned from the management (6) let the police took the perpetrator and gave sanctions to students who involved and (7) updated the UII’s website (www.uii.ac.id) with positive press and remove news / releases about Mapala UNISI.Keywords: crisis, management, UII